Design Research and Planning Practice of Non-legacy Creative Products in Liaoning Region under the Dynamic Inheritance - Liu, Yi (Transactions on Economics, Business and Management Research, 2023)
Taking the "living inheritance" of intangible cultural heritage as the research direction, this paper conducts a detailed investigation and analysis of the intangible cultural heritage in Liaoning region. First, it will sort out the performance characteristics of regional intangible cultural heritage, extract symbolic graphic symbols, and explore the path of living cultural inheritance under the background of new media era while analyzing and studying the characteristics of Liaoning culture and intangible cultural folklore. The second is to present a complete and systematic regional cultural identification system in the form of data platform construction, and improve the collection, sorting and innovative design of regional cultural symbols; The third is to focus on the living inheritance of intangible cultural heritage, design and apply cultural and creative products according to different intangible cultural heritage themes, and commit to serving local economic development and exploring the exploration road of the living inheritance of social intangible cultural heritage.